Analisis Kelayakan Usaha Tani Bawang Merah di Desa Kateng Kecamatan Praya Barat Kabupaten Lombok Tengah - Nirmawati Nirmawati (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The purpose of this study was to know the income of farmers on shallot farming, ²to to know whether or not shallot farming is feasible or not to be carried out in Kateng Village Praya West District, Central Lombok Regency. The research method used to determine the sample is descriptive method to analyze the feasibility of onion farming analyzed by BEP and R/C Ratio. Determination of the sample is done by simple random sampling with a total sample of 20 people. Data collection in this study consisted of primary data and secondary data. The results of the study concluded that the average income of shallot farmers in Kateng Village, West Praya District, Central Lombok Regency was Rp. 2,703,000 with a land area of 0.31 Ha in one growing season. Based on the feasibility analysis of onion farming in Kateng Village, West Praya District, Central Lombok Regency, it was declared feasible to cultivate because R/C 1.30 > 1.